Advances in the immunoescape mechanisms exploited by alphaherpesviruses - Wang, Yimin; Ma, Caoyuan; Wang, Shan; Wu, Hongxia; Chen, Xuanqi; Ma, Jinyou; Wang, Lei; Qiu, Hua-Ji; Sun, Yuan (Frontiers in Microbiology, 2024)
Alphaherpesviruses, categorized as viruses with linear DNA composed of two complementary strands, can potentially to induce diseases in both humans and animals as pathogens. Mature viral particles comprise of a core, capsid, tegument, and envelope. While herpesvirus infection can elicit robust immune and inflammatory reactions in the host, its persistence stems from its prolonged interaction with the host, fostering a diverse array of immunoescape mechanisms. In recent years, significant advancements have been achieved in comprehending the immunoescape tactics employed by alphaherpesviruses, including pseudorabies virus (PRV), herpes simplex virus (HSV), varicella-zoster virus (VZV), feline herpesvirus (FeHV-1), equine herpesvirus (EHV-1), and goat herpesvirus type I (CPHV-1). Researchers have unveiled the intricate adaptive mechanisms existing between viruses and their natural hosts. This review endeavors to illuminate the research advancements concerning the immunoescape mechanisms of alphaherpesviruses by delineating the pertinent proteins and genes involved in virus immunity. It aims to furnish valuable insights for further research on related mechanisms and vaccine development, ultimately contributing to virus control and containment efforts.